2021
DOI: 10.3390/v13050851
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Morogoro Virus Infection in Its Natural Host, Mastomys natalensis

Abstract: Natural hosts of most arenaviruses are rodents. The human-pathogenic Lassa virus and several non-pathogenic arenaviruses such as Morogoro virus (MORV) share the same host species, namely Mastomys natalensis (M. natalensis). In this study, we investigated the history of infection and virus transmission within the natural host population. To this end, we infected M. natalensis at different ages with MORV and measured the health status of the animals, virus load in blood and organs, the development of virus-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 49 publications
5
23
0
Order By: Relevance
“…The age of the animals at the time of infection should be emphasized. It has been repeatedly shown that M. natalensis and other rodents that are infected with arenaviruses in utero , perinatally or in neonatal stages postpartum, remain persistently infected and shed virus in urine for long periods [ 23–26 ], which also holds true for LASV, as preliminary studies demonstrated [ 14 ]. Likewise, heterologous LASV infection in neonatal M. musculus resulted in prolonged shedding in the urine [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The age of the animals at the time of infection should be emphasized. It has been repeatedly shown that M. natalensis and other rodents that are infected with arenaviruses in utero , perinatally or in neonatal stages postpartum, remain persistently infected and shed virus in urine for long periods [ 23–26 ], which also holds true for LASV, as preliminary studies demonstrated [ 14 ]. Likewise, heterologous LASV infection in neonatal M. musculus resulted in prolonged shedding in the urine [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, persistent infection and shedding after vertical transmission or early postpartum infection is a plausible mode of maintenance of LASV in wild populations of M. natalensis and remains a potential source of rodent-to-human transmission. For the LASV-related Morogoro virus, horizontal transmission to neonates of M. natalensis from persistently infected individuals reduced the chance of persistent infection with this LASV-related arenavirus by 20–60% compared to s.c.-inoculation at day two after birth [ 23 ]. Likewise, the inoculation route might be a major factor in LASV persistence and needs to be thoroughly considered if experimental data are to be applied to virus transmission in a wild population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, persistent infection as a mechanism of maintenance in the reservoir population may depend on the age of infection. For arenaviruses such as Guanarito mammarenavirus , JUNV, LASV, LCMV, MACV, and Morogoro virus, studies have shown an age-dependency in the duration of infection among reservoir hosts [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ]. Neonates develop long-term viral persistence, while adults can clear infection [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ].…”
Section: What Biological Strategies Have Evolved That Allow Rna Viruses To Reside In Bats and Rodents?mentioning
confidence: 99%
“…For arenaviruses such as Guanarito mammarenavirus , JUNV, LASV, LCMV, MACV, and Morogoro virus, studies have shown an age-dependency in the duration of infection among reservoir hosts [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ]. Neonates develop long-term viral persistence, while adults can clear infection [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ]. The mechanism by which virus persists or is cleared is an area in need of additional investigation.…”
Section: What Biological Strategies Have Evolved That Allow Rna Viruses To Reside In Bats and Rodents?mentioning
confidence: 99%